Personal Data Protection and Anonymization in the Process of Data Commodity Trading. (August 2020) - Su, Jing; Gai, Jiale; Si, Yaqing; Zheng, Xinyu; Li, Guangkai; Liu, Zhixue
Abstract: Big data brings tremendous commercial value, but at the same time, it also leads to personal information leakage and other problem. This paper analyses the laws and regulations of the personal information and anonymization at home and abroad, and discusses the legal identification criterion of personal information, personal data and data anonymization systematically. And combining with the practice, this paper provides general methods for anonymizing data with personal privacy when they are used or traded by companies.